Pre-pregnancy migraine diagnosis, medication use, and spontaneous abortion: a prospective cohort study - Holly M. Crowe; Amelia K. Wesselink; Lauren A. Wise; Susan S. Jick; Kenneth J. Rothman; Ellen M. Mikkelsen; Henrik T. Sørensen; Elizabeth E. Hatch (The Journal of Headache and Pain, 2022)
Abstract Background Migraine is common among females of reproductive age (estimated prevalence:17–24%) and may be associated with reproductive health through underlying central nervous system excitability, autoimmune conditions, and autonomic dysfunction. We evaluated the extent to which pre-pregnancy migraine diagnosis and medication use are associated with risk of spontaneous abortion (SAB). Methods We analyzed data from a preconception study of pregnancy planners (2013–2021). Eligible participants self-identified as female, were aged 21–45 years, resided in the USA or Canada, and conceived during follow-up (n = 7890). Participants completed baseline and bimonthly follow-up questionnaires for up to 12 months or until a reported pregnancy, whichever occurred first. Pregnant participants then completed questionnaires during early (~ 8–9 weeks) and late (~ 32 weeks) gestation. We defined migraineurs as participants who reported a migraine diagnosis or use of a medication to treat migraine. Preconception questionnaires elicited migraine medication use during the past 4 weeks, and SAB on follow-up and pregnancy questionnaires. We used Cox regression models with gestational weeks as the time scale to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations among preconception migraine, migraine medication use, and SAB, controlling for potential demographic, medical, and lifestyle confounders. Results Nineteen percent of study pregnancies ended in SAB. History of migraine before conception was not appreciably associated with SAB risk (HR = 1.03, 95% CI: 0.91–1.06). Use of any migraine medication was associated with a modest increase in SAB risk overall (HR = 1.14, 95% CI: 0.96–1.36). We observed the greatest increase in risk among those taking migraine medications daily (HR = 1.38, 95% CI: 0.81–2.35) and those taking prescription migraine prophylaxis (HR = 1.43, 95% CI: 0.72–2.84) or combination analgesic and caffeine medications (HR = 1.42, 95% CI: 0.99–2.04). Conclusions Migraine medication use patterns suggesting greater underlying migraine severity were associated with increased risk of SAB. This research adds to the limited information available on the reproductive effects of migraine.